Computer Games Fourth Workshop on Computer Games, CGW 2015, and the Fourth Workshop on General Intelligence in Game-Playing Agents, GIGA 2015, Held in Conjunction with the 24th International Conference on Artificial Intelligence, IJCAI 2015, Buenos Aires, Argentina, July 26-27, 2015, Revised Selected Papers - Cazenave, Tristan; Winands, Mark H.M.; Edelkamp, Stefan; Schiffel, Stephan; Thielscher, Michael; Togelius, Julian; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book constitutes the refereed proceedings of the Fourth Computer Games Workshop, CGW 2015, and the Fourth Workshop on General Intelligence in Game-Playing Agents, GIGA 2015, held in conjunction with the 24th International Conference on Artificial Intelligence, IJCAI 2015, Buenos Aires, Argentina, in July 2015. The 12 revised full papers presented were carefully reviewed and selected from 27 submissions. The papers address all aspects of artificial intelligence and computer game playing. They discuss topics such as Monte-Carlo methods; heuristic search; board games; card games; video games; perfect and imperfect information games; puzzles and single player games; multi-player games; combinatorial game theory; applications; computational creativity; computational game theory; evaluation and analysis; game design; knowledge representation; machine learning; multi-agent systems; opponent modeling; planning; reasoning; search.
Keywords: Computer science; Computers; Computer science -- Mathematics; Artificial intelligence; Personal computers; Computer Science; Artificial Intelligence (incl. Robotics).; Personal Computing; Mathematics of Computing; Theory of Computation; Electronic books